Characteristics of global potential natural vegetation distribution from 1911 to 2000 based on comprehensive sequential classification system approach. (18th June 2013) - Feng, Qisheng; Liang, Tiangang; Huang, Xiaodong; Lin, Huilong; Xie, Hongjie; Ren, Jizhou
Abstract: Bioclimatology based vegetation classification models play an important role in the response of terrestrial ecosystems to global climate change. In this paper, three periods (1911–1940, 1941–1970 and 1971–2000) of Potential Natural Vegetation (PNV) maps were created based on the CSCS (Comprehensive Sequential Classification System) model and the CRU_TS 2.1 datasets. A model of the mean center was used to calculate the shift distance and direction for each broad vegetation category during the three periods. Results indicate that: (i) the area of tundra and alpine steppe and desert decreased by 5.1 and 5.5%, while the area of forest and grassland increased by 2.3 and 3.8% from 1911 to 2000 at global scale, respectively. However, there was a significant difference in the magnitude of area change in northern and southern hemispheres. And (ii) the tundra and alpine steppe, semi‐desert, savanna, temperate forest and subtropical forest shifted towards the poles; the frigid desert and temperate humid grassland shifted towards the equator, while the warm desert shifted towards southwest, the tropical forest shifted towards southwest in the northern hemisphere and southeast in the southern hemisphere, and the steppe shifted towards northeast in the northern hemisphere and northwest in the southern hemisphere. The shift distance of the warm desert in the southern hemisphere was the largest among the 10 broad vegetation categories.